Optimal Treatment for Intermediate- and High-Risk, Nonmuscle-Invasive Bladder Cancer - A.P.M. van der Meijden (The Scientific World Journal)
According to clinical and pathological factors the prognosis of a patient with non-muscle invasive bladder tumors can be assessed. The prognosis is determined by the likelihood of recurrence(30-70%) and/or progression to muscle invasive bladder cancer(1-15%).Trans urethral resection of bladder tumors remains the initial therapy but adjuvant intravesical instillations are necessary.All patients benefit from a single immediate post operative instillation with a chemotherapeutic agent and for low risk tumors this is the optimal therapy.Patients with intermediate and high risk tumors need more intravesical chemo-or immunotherapy. Chemotherapy reduces recurrences but not progression. Intravesical immunotherapy(BCG) prevents or delays progression. Patients at high risk for progression may need upfront cystectomy.